Hubungan Motivasi, Harga Diri, dan Kepercayaan Diri Terhadap Keberhasilan Siswa Belajar Matematika [Correlation Between Motivation, Self-Esteem, and Self Confidence to Student’s Success in Studying Mathematics] - Hikmah Nata Rabay (Magister Teknologi Pendidikan Fakultas Ilmu Pendidikan, Universitas Pelita Harapan, 2021)
The success of students learning Mathematics at “X” Junior High School is very low. Alike success of students learning Mathematics, the students also have low motivation, low self-esteem, and low self-confidence. According to this fact, guessed that there is correlation between motivation and success of students, between self-esteem and success of students, and between self-confidence and success of students learning Mathematics, so needed a research to see that correlation. Research method that was used to see that correlation is correlation method, with questionnaire as a tool to collect data from 131 students of “X” Junior High School. Technique used to analyze data are statistical techniques, which are descriptive and inferential statistic. The conclusions are 1) there is a significant correlation between motivation and success of students learning Mathematics at “X” Junior High School, 2) there is significant correlation between self-esteem and success of students learning Mathematics at “X” Junior High School, and 3) there is significant correlation between self-confidence and success of students learning Mathematics at “X” Junior High School.